State support of domestic tourism in the context of the COVID-19 consequences and financial constraints - Baranova, Ekaterina; Stytsyuk, Rita; Makushkin, Sergey; Shelygov, Aleksandr; Ukhina, Tatiana; Stepanova, Diana (Anais Brasileiros de Estudos Turísticos, 2023)
Tourism is a sector that constitutes a significant part of many economies. Over the years, the tourism sector has proven its resilience and ability not only to recover from economic crises but also to contribute to economic and social recovery. The article aims at proposing practical measures for the state support of tourism activities in Russia in the context of the COVID-19 consequences and financial constraints on business. The study considers the measures taken in different countries to promote the development of domestic tourism in a pandemic. Based on an expert survey, state support measures for the development of domestic tourism are proposed as the most sustainable socio-economic model of tourism in the context of the post-COVID restrictions and imposed sanctions. It has been concluded that the reorientation and development of domestic tourism is, among other things, a type of adaptation that is necessary for Russian tourism and the economy to overcome the coronavirus consequences and the financial constraints of business.